Community Stigma toward Leprosy Patients - Hidayat, Mukhlish; Hakim, Arif Rahman; Khalilah, Nur; Nur, Mohamad; Dewi, Novela Eka Candra; Rohman, Atiqur (Universitas Nurul Jadid, 2025)
Leprosy is a chronic disease that rarely causes death but often causes disability. This disability leads to different opinions in the community, which disrupts the social life of leprosy sufferers and the surrounding community. In this study, the researcher wanted to examine more deeply the opinions of people with leprosy. This research design uses qualitative research that focuses on a phenomenological approach. The participants taken in this study were 11 people who had criteria where the location of the participant's house was not more than 100 meters from the leprosy patient. Participants were selected through purposive sampling and data collection techniques using in-depth interviews with the main instrument, namely the researcher himself and assisted by other instruments in the form of field notes, interview guidelines and sound recording devices. The results of this study resulted in three themes: (1) Factors that influence stigma towards leprosy patients (2) Perceptions of Leprosy Patients (3) Forms of Stigma towards Leprosy Patients. Community stigma still occurs against leprosy patients, this is due to the low level of education and knowledge of the community about leprosy, so there needs to be intervention by health workers to increase community knowledge so that the stigma felt by leprosy patients can be reduced.